Analysis of Broiler Chicken Farming Income in Open House Partnership Scheme in Dampang Village, Gantarang Subdistrict, Bulukumba Regency - Mihrani Mihrani (Citakonsultindo, 2023)
This study aims to determine the income of broiler chicken farmers in the open house partnership scheme in Dampang Village, Gantarang Subdistrict, Bulukumba Regency. The population of broiler chicken farmers utilizing this partnership scheme in Dampang Village, Gantarang Subdistrict, Bulukumba Regency, consists of seven individuals. The research employed a census approach, where the entire population was considered as the sample, and a quantitative method was used. The study results revealed the income earned by the farmers over three periods in Dampang Village, Gantarang Subdistrict, Bulukumba Regency, as follows: Respondent 1, with a population of 4000, earned Rp. 61,815,283; Respondent 2, with a population of 2500, earned Rp. 53,008,671; Respondent 3, with a population of 4000, earned Rp. 55,974,445; Respondent 4, with a population of 3500, earned Rp. 65,794,186; Respondent 5, with a population of 5000, earned Rp. 82,527,734; Respondent 6, with a population of 2500, earned Rp. 35,764,064; and Respondent 7, with a population of 3000, earned Rp. 60,972,701.